Effect of clutch lining frictional characteristics on take-up judder. (September 2017) - Gkinis, T; Rahmani, Ramin; Rahnejat, H
Take-up judder is the first rigid body torsional mode of the clutch system, which occurs during clutch engagement. This phenomenon is induced by stick-slip oscillations at the friction lining interfaces between the clutch disc and flywheel, and the pressure plate. The phenomenon is influenced by the clutch lining friction characteristics, the topography of the mating-sliding surfaces, and the operational conditions during the engagement process. Therefore, the interfacial characteristics are affected by contact pressure, interfacial slip speed, and surface temperature. Take-up judder causes driver and vehicle occupant discomfort, as well as gradual wear of contacting surfaces. The response frequency of the system is reported to be in the range 5–20 Hz, depending on the clutch system and vehicle inertia. In this paper, the measured interfacial friction characteristics together with clamp load variation (contact pressure) under different surface temperatures are included in a multi-degree of freedom dynamic analysis to obtain torsional vibrations of the system, pertaining to take-up judder conditions. Such an in-depth investigation has not hitherto been reported in literature. The paper shows that take-up judder is omnipresent under all clutch engagement conditions, but its poignancy is most evident at cold surface temperatures. It is also shown that the transient judder response has a broader spectral content that is generally acknowledged.